Behavioural land use policy studies: Past, present, and future. (April 2022) - Bao, Helen X.H.; Robinson, Guy M.
Abstract: In this introduction to the themed issue, "Behavioural Land Use Policy Studies", we firstly provide a brief review of the current state of behavioural studies in land use policy, followed by a discussion of behavioural biases that are most relevant to land use policymaking. Next, we summarise the seven papers included in this themed issue. The behavioural topics explored by these papers include endowment effect, prospect theory, nudge, trust, social norms, time preference, and loss aversion. Our review of the literature examines the role played by Land Use Policy in applications of behavioural insights in environmental studies in general and land use policy studies in particular. The papers included in this themed issue push this research frontier by using large survey datasets from the field, and by investigating some under-researched behavioural tools (e.g., nudge). We conclude by suggesting research gaps to be filled by future behavioural land use policy studies. Highlights: Behavioural insights in land use policy studies are growing in importance. Behavioural insights can make significant impacts on decisions in public policies. Key ideas include nudge theory, trust, endowment effects and social norms. Land Use Policy has promoted and explored applications of behavioural insights. Future behavioural studies require a large sampling frame to examine government policy.